Website Technology Implementation in Stock Management for Enhanced Operational Efficiency: Bismika Tani Case Study - Ahmadi, Thoriq; Jazuli, Ahmad; Fiati, Rina (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
This study develops a web-based Stock and Sales Management Information System to improve accuracy, speed up transactions, and support real-time reporting in the retail sector. This system includes recording incoming and outgoing stock, product registration, sales recording, and report generation, and applies the Just-In-Time (JIT) concept to reduce excess stock and storage costs. Developed using the Waterfall method, the design uses UML, and is implemented with PHP Native and MySQL. Usability testing using the System Usability Scale (SUS) obtained a total sco re of 815 from 9 respondents, with an average of 90.56, categorized as "Excellent" with a value of "A", indicating that the system is very user-friendly and efficient. The real-time reporting feature increases transparency and makes it easier for store owners to monitor stock and transactions. Overall, this system offers a practical and effective solution for retail businesses in managing stock and sales optimally.Kata kunci: Data Transparency; Just-In-Time; MySQL; Operational Efficiency; PHP Native AbstrakPenelitian ini mengembangkan Sistem Informasi Manajemen Stok dan Penjualan berbasis web untuk meningkatkan akurasi, mempercepat transaksi, dan mendukung pelaporan real-time di sektor ritel. Sistem ini meliputi pencatatan stok masuk dan keluar, registrasi produk, pencatatan penjualan, dan pembuatan laporan, serta menerapkan konsep Just-In-Time (JIT) untuk mengurangi kelebihan stok dan biaya penyimpanan. Dikembangkan menggunakan metode Waterfall, perancangan menggunakan UML, dan diimplementasikan dengan PHP Native dan MySQL. Pengujian usability menggunakan System Usability Scale (SUS) memperoleh skor total 815 dari 9 responden, dengan rata-rata 90,56, dikategorikan "Sangat Baik" dengan nilai "A", yang menunjukkan bahwa sistem sangat ramah pengguna dan efisien. Fitur pelaporan real-time meningkatkan transparansi dan memudahkan pemilik toko untuk memantau stok dan transaksi. Secara keseluruhan, sistem ini menawarkan solusi praktis dan efektif bagi bisnis ritel dalam mengelola stok dan penjualan secara optimal.